The slope-intercept form of a linear equation is given by:
\[ y = mx + b \]
where:
- \( y \) is the dependent variable,
- \( m \) is the slope,
- \( x \) is the independent variable, and
- \( b \) is the y-intercept.
To rearrange this equation for \( x \), we can follow these steps:
-
Isolate the term containing \( x \): Start by subtracting \( b \) from both sides of the equation:
\[ y - b = mx \]
-
Solve for \( x \): Now, to isolate \( x \), divide both sides of the equation by \( m \):
\[ x = \frac{y - b}{m} \]
Now we have rearranged the slope formula \( y = mx + b \) to express \( x \) in terms of \( y \), \( m \), and \( b \):
\[ x = \frac{y - b}{m} \]